A model-based reconstruction of recent Siberian climate - focusing on snow cover - Klehmet, Katharina (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2014)
Snow cover is an important feature of the terrestrial landscape in Siberia. Variability and changes of snow cover have profound implications for surface energy and water balance, first due to its high short-wave albedo, high thermal emissivity and low heat conductivity, and second due to the control of evaporation, water storage, soil moisture, river discharge and freshwater transport. The snow properties affect moreover the soil temperature and thus the thermal state of permafrost and the biogeochemical cycle. Monitoring of Siberian climate parameters, including those for snow cover, is complicated by the lack of in situ measurements, especially in the arctic regions. The sparse station density and limited length of data records makes it difficult to obtain a detailed regional overview of past and ongoing changes. The need of long-term climate information with less spatial and temporal gaps has motivated the effort to generate a model-based reconstruction of recent Siberian climate using the regional model COSMO-CLM (CCLM). Although CCLM has been used for several areas, no simulations have been conducted for Siberia before. Therefore, different sensitivity experiments have been performed to identify important regional-specific processes and related adjustments that can be used for a specific model configuration for Siberia. These adjustments are an increased soil column depth down to 92m, the application of the multi-layer snow model and the reduction of the minimal heat diffusion that has implications on the turbulence parameterization to better account for the stable conditions during the winter high pressure system. One hindcast simulation has been conducted from 1948-2010 at about 50 km grid spacing using NCEP-R1 as driving global reanalysis to obtain a reconstruction of 63 years and to investigate long-term regional changes of climate parameters focusing on snow cover. A second climate reconstruction has been performed for comparison using ERA-40 reanalysis as forcing that range from 1958-2001. In terms of ...